(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Slum life has never been easy for the slum women insofar as housing and living conditions are concerned. In slums across the world, there is a noticeable lack of basic infrastructure, services, and basic shelter. They experience varying deprivations and risks, which can include a lack of durable housing, overcrowding, insufficient access to clean water, poor sanitation, and threats of forced evictions. Women living in slums are often susceptible to forced evictions by governments and other actors, and too often face gender-based violence before, during, and after eviction. . Women and girls often suffer the worst effects. Women and girls in urban India are also at high risk of gender-based violence. On this backdrop, this study is trying to understand a Women’s Empowerment and Vulnerability in Slums of Ichalkarani.